Clinical Benefits and Safety of FMS-Like Tyrosine Kinase 3 Inhibitors in Various Treatment Stages of Acute Myeloid Leukemia: A Systematic Review, Meta-Analysis, and Network Meta-Analysis - Xu, Qingyu; He, Shujiao; Yu, Li (Frontiers in Oncology, 2021)
Background: Given the controversial roles of FMS-like tyrosine kinase 3 inhibitors (FLT3i) in various treatment stages of acute myeloid leukemia (AML), this study was designed to assess this problem and further explored which FLT3i worked more effectively. Methods: A systematic review, meta-analysis and network meta-analysis (NMA) were conducted by filtering PubMed, Embase, Cochrane library, and Chinese databases. We included studies comparing therapeutic effects between FLT3i and non-FLT3i group in AML, particularly FLT3(+) patients, or demonstrating the efficiency of allogeneic hematopoietic stem cell transplantation (allo-HSCT) in FLT3(+) AML. Relative risk (RR) with 95% confidence intervals (CI) was used for estimating complete remission (CR), early death and toxicity. Hazard ratio (HR) was used to assess overall survival (OS), event-free survival (EFS), relapse-free survival (RFS) and cumulative incidence of relapse (CIR). Results: After addressing all criteria, 39 studies were eventually analyzed. Better CR was accomplished by FLT3i in untreated AML (RR 0.88, p = 0.04) and refractory and relapsed FLT3(+) AML (rrAML) (RR 0.61, p < 0.01) compared to non-FLT3i arm, followed by improved survival (untreated AML: OS, HR 0.76; EFS, HR 0.67; RFS, HR 0.72; all p < 0.01; FLT3(+) rrAML: OS, HR 0.60, p < 0.01; RFS, HR 0.40, p = 0.01). In addition, allo-HSCT improved survival in FLT3(+) AML (OS, HR 0.53; EFS, HR 0.50; RFS, HR 0.57; CIR, HR 0.26; all p < 0.01), which was further prolonged by FLT3i administrated after allo-HSCT (OS, HR 0.45; RFS, HR 0.34; CIR, HR 0.32; all p < 0.01). Additionally, FLT3i consistently improved OS (p < 0.05) regardless of FLT3-ITD ratio, when compared to non-FLT3i group. Besides, FLT3i showed significantly increased risk of thrombocytopenia, neutropenia, anemia, skin- and cardiac-related adverse effects, increased alanine aminotransferase, and increased risk of cough and dyspnea (p < 0.05). In NMA, gilteritinib showed the highest probability for improved prognosis. Conclusions: FLT3i safely improved prognosis in induction/reinduction stage of FLT3(+) AML and further boosted survival benefits from allo-HSCT as maintenance therapy, suggesting better prognosis if FLT3i is combined before and after allo-HSCT. In NMA, gilteritinib potentially achieved the best prognosis, which should be identified in direct trials.